HUBUNGAN DUKUNGAN SUAMI DENGAN PEMBERIAN ASI EKSKLUSIF DI DAERAH PERDESAAN - Novira Kusumayanti; Triska Susila Nindya (Media Gizi Indonesia, 2017)
Exclusive breastfeeding could decrease infant mortality. Exclusive breastfeeding coverage in Indonesia is still low. Many factors affect exclusive breastfeeding including husband support. Husband support contribute to maternal emotion that affect the smooth refl exes of breast milk production. This study aimed to determine the relationship of husband support and exclusive breastfeeding in the Kademangan district, Blitar. This is cross sectional study. Interview was done to 66 breastfeed mothers with infants aged 6–12 months. The sample was taken by simple random sampling. Location of this study was six villages in Kademangan district, Blitar and conducted in October 2016. Bivariate analysis was performed by Spearman correlation test. The prevalence of exclusive breastfeeding was 21.2%. Most of husband support exclusive breastfeeding. Based on cross tabulation, mother who gave breastfeeding to their children was higher when they are supported by their husband. Eventhough Spearman correlation test showed no signifi cant relationship between husband support and exclusive breastfeeding. Mothers who had support from their husband had a higher proportion of giving exclusive breastfeeding than had not supported by their husband, eventhough not statistically signifi cant correlated.